2014
DOI: 10.1557/opl.2014.15
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Photoluminescence of Sulfur-Bridged Organic Chromophores

Abstract: A general approach to enhancing the photoluminescent quantum yield for a series of organic chromophores is presented. By bridging a chromophore symmetrically about a sulfur atom it was found that the photoluminescence could be systematically increased by oxidizing the bridge. Furthermore, the enhanced quantum yields were achieved without diminishing the solubility of these chromophores in common organic solvents. The photophysical characterization, as well as potential applications of these molecules will be d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…Compared with their emission from solution, the solid-state emissions are remarkably red-shifted more than 50 nm, and the efficiencies also a little lowered, which could be due to the strong intermolecular interaction at the aggregate form [12]. However, these PL efficiency value are still comparable with those of reported dibenzothiophene S,S-dioxides derivatives [6]. a Photophysical measurements in hexane (5.0 Â 10 À6 mol L À1 ) b l abs is the strong absorption peak appearing at the longest wavelength.…”
Section: Uv-vis Absorption and Fluorescence Emissionmentioning
confidence: 79%
See 3 more Smart Citations
“…Compared with their emission from solution, the solid-state emissions are remarkably red-shifted more than 50 nm, and the efficiencies also a little lowered, which could be due to the strong intermolecular interaction at the aggregate form [12]. However, these PL efficiency value are still comparable with those of reported dibenzothiophene S,S-dioxides derivatives [6]. a Photophysical measurements in hexane (5.0 Â 10 À6 mol L À1 ) b l abs is the strong absorption peak appearing at the longest wavelength.…”
Section: Uv-vis Absorption and Fluorescence Emissionmentioning
confidence: 79%
“…Two approaches have been generally applied to synthesize arylsulfones: post-oxidization, where the sulfide-bridged system is first synthesized and then oxidized [6]; and the pre-oxidization, where benzothiophene S,S-dioxides are first synthesized and then coupled with other reactant to build larger sulfone-bridged structures [10,11]. For example, Nandakumar et al recently reported the synthesis of substituted dibenzothiophenes S,Sdioxides via a Diels-Alder reaction between 1,3-diarylbenzo[c] furans and thiophene S,S-dioxide derivatives [11].…”
Section: Synthesis and Structuresmentioning
confidence: 99%
See 2 more Smart Citations
“…To address this problem, the opposite of ACQ, aggregation-induced emission (AIE) effect which was first reported by Tang [31] paves a facile way for the design and synthesis of efficient solid-state materials. Remarkably, sulfonecontaining materials are receiving increasing attention due to their effectively enhanced photoluminescence quantum yields [32,33]. Adachi and coworkers have reported amount of TPAsulfone derivatives with interesting thermal activated delayed fluorescence (TADF) properties, ascribed to the small energy gap between the lowest single (S 1 ) and the lowest triplet (T 1 ) states resulting in strong reverse intersystem crossing (RISC) process [34e37].…”
mentioning
confidence: 99%